Spatial characteristics analysis of sectoral carbon transfer path in international trade: A comparison of the United States and China. (1st October 2022) - Xu, Dongxiao; Li, Yaoguang; Zhao, Mingyuan; Wang, Xinjing; Zhang, Yan; Chen, Bin; Yang, Zhifeng
Highlights: Nine cross border CO2 transfer types are been divided based on geographical features. Each path consists of primary & final production sectors and final consumption. Path analysis results can serve for further precise mitigation plans. Abstract: CO2 transfers induced by international trade account for nearly a quarter of total CO2 emissions, becoming the hotspots of global carbon mitigation. However, current analysis paid little attention to the spatial characteristics and multiple roles of the international sector, making it difficult to serve mitigation policies quantitatively. In this study, we built a CO2 transfer framework, in which the path flowed through the primary production sector, final production sector, and final consumption. We considered the domestic and foreign location differentiation to divide import and export transfers into nine spatial patterns. We figured out critical paths that influenced the total exports and imports, respectively, traced their temporal variation as well. Primary production export and import transfers with single foreign countries were the most significant transfer types in China and the United States, respectively, both with an average share of about 35%. In the key export and import paths, Transportation in the United States, and Electricity, Gas, and Water in China (both accounting for about half of the total export transfers) acting as primary production sectors had close export connections with foreign Electrical and Machinery sectors and Construction; the US's Public Administration and the China's Construction (about 1/4 and 1/3 of the total import transfers) acting as final production sector had close import associations with foreign Transportation sectors and Electricity, Gas and Water sectors, respectively. The results can lay a foundation for further macro mitigation regulation and precise sectoral reduction plans.